2017
DOI: 10.1007/s10853-017-1216-1
|View full text |Cite
|
Sign up to set email alerts
|

Doping mechanisms and electrical properties of bismuth tantalate fluorites

Abstract: Phase-pure bismuth tantalate fluorites were successfully prepared via conventional solid-state method at 900 °C in 24-48 h. The subsolidus solution was proposed with the general formula of Bi3+x Ta1−x O7−x (0 ≤ x ≤ 0.184), wherein the formation mechanism involved a one-toone replacement of Ta5+ cation by Bi3+ cation within ~4.6 mol% difference. These samples crystallised in a cubic symmetry, space group Fm-3 m with lattice constants, a = b = c in the range 5.4477(± 0.0037)-5.4580(± 0.0039) Å. A slight incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the charge has been reasonably explained to be balanced by the change in the occupancy of O sites in previous studies. 5 Therefore, it can be concluded that by mixing Bi 2 O 3 and Ta 2 O 5 at a molar ratio of Ta/Bi = 0.1, 0.33, the resulting Bi–Ta oxides stabilized and formed a substitutional solid solution with the cubic crystal phase.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, the charge has been reasonably explained to be balanced by the change in the occupancy of O sites in previous studies. 5 Therefore, it can be concluded that by mixing Bi 2 O 3 and Ta 2 O 5 at a molar ratio of Ta/Bi = 0.1, 0.33, the resulting Bi–Ta oxides stabilized and formed a substitutional solid solution with the cubic crystal phase.…”
Section: Resultsmentioning
confidence: 98%
“…Bi 2 O 3 is one of the polymorphous oxides, and is employed in a broad range of applications such as solid-state electrocatalysis, [1][2][3][4][5][6] inorganic orange pigment, 7 and photocatalytic reactions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] To date, four different crystal phases have been reported: a phase (monoclinic), b phase (tetragonal), g phase (cubic), and d phase (cubic).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, substitution with various suitable ions (Nb 5+ , Mo 6+ , Ta 5+ , Ti 4+ , W 6+ etc.) is usually used [1][2][3][4]. It is found for Bi 2 O 3 -WO 3 system that the introduction of tungsten oxide (more than 9 wt.%) is a necessary condition for stabilization of δ-phase Bi 2 O 3 [5].…”
Section: Introductionmentioning
confidence: 99%